Relationship of oestrogen receptor alpha gene polymorphisms with risk for benign prostatic hyperplasia and prostate cancer in Chinese men. Issue 13 (March 2017) - Han, Zihua; Zhang, Lingzhi; Zhu, Rujian; Luo, Lifei; Zhu, Min; Fan, Lilong; Wang, Guanfu
Abstract : Abstract: The relationship of oestrogen receptor with benign prostatic hyperplasia (BPH) and prostate cancer (PC) is not clear at present. This study aimed to investigate the molecular mechanism underlying the occurrence and development of BPH and prostate. Two hundred forty-four PC cases, 260 BPH patients, and 222 healthy men were recruited from Han people in China, and the oestrogen receptor alpha (ESRα) gene polymorphism (rs2234693 [PvuII] and rs9340799 [XbaI]) on intron 1 was determined. The relationship of gene polymorphism with PC and BPH was evaluated with Logistic regression, and the linkage disequilibrium and haplotyping were assessed with SHEsis software. The risk for PC in BPH patients with PvuII C allele was higher (OR = 1.437, 95% CI: 1.110–1.859), but the differentiation degree of cancer cells was relatively better in PC patients with PvuII C allele (OR = 0.419, 95% CI: 0.285–0.616), and most of them are circumscribed (OR = 0.706, 95% CI: 0.485–1.02). There was significant linkage disequilibrium between PvuII and XbaI. The genotype TTAG not only induced BPH (OR = 6.260, 95% CI: 1.407–27.852), but increased the risk for PC (OR = 6.696, 95% CI: 1.504–29.801). However, the genotype TTAG in BPH patients had no relationship with the risk for PC ( P > 0.05). Furthermore, men with haplotype TG were more likely to suffer PC (OR = 9.168, 95% CI: 2.393–35.119), but men with haplotype TA and enlarged prostate had a low risk for PC (OR = 0.708, 95% CI: 0.551–0.912). These results show the relationship between ESRα gene polymorphism and susceptibility to PC and BPH in Chinese men, and the ethnic and regional difference as well.